PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI NEGERI SIPIL PADA DINAS SOSIAL DAN TENAGA KERJA KABUPATEN BADUNG - Kadek Lusigita (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2017)
The Government as an organization that show high public service performance must be supported by the human resources. The human resources has an important role as implementer of several activities that organized by the organization to achives the goals. The research objective was to determine the effect of leadership on work satisfaction, work discipline on work satisfaction, leadership on employee performance, work discipline on employee performance and work satisfaction on employee performance of social and workforce offices employee in Badung regency. The population of this study is all the public employee of social and workforce office in Badung regency. The amount of public employee is 89 persons. Analyzing method that used is structural equation modeling–SEM method based on variance or component base SEM, that known as partial least square (PLS). the result of this study are leadership has positive and significant impact on the employee satisfaction, work discipline has positive and not significant impact on the employee satisfaction, leadership has positive and not significant impact on the employee performance, work discipline has positive and significant impact on the employee performance, work satisfaction has positive and significant impact on employee performance.